Conflict Resolution of Regional Head Election (PILKADA) Buru Selatan District in 2015 - Muhammad Jafar Loilatu; Yana Syafrieyana Hijir; Vina Salviana (Journal of Local Government Issues (LOGOS), 2018)
The first round of simultaneous elections in 2015 included 269 regions. South Buru Regency participated in organizing the democratic party. South Buru regency elections that ended the conflict were followed by two candidate pairs Rivai Fatsey, S. STP., MPA & Drs. Anthonius Lesnusa, MM (HIKMAT) and Tagop Sudarsono Soulisa, SH., MT & Ayub Seleky, SH., MH (TOP-BU). Conflict resolution involves both HIKMAT and TOP-BU voters who are involved in the conflict with government institutionalization and local wisdom, the local kerafina approach with the aim of eliminating the politicization of customary law so that potential conflicts do not reappear. Another approach used is a familial approach in order to eliminate judgment, on the other hand, support from the government by accommodating the demands of both parties. Through the tradition of local equality and innervation, this conflict can be resolved or by using positive peace, the institutionalization of these values can influence the behavior of both parties so as not to create new conflicts. The meeting point of this conflict was the return of conflict victims and the return of non-permanent employees.Keywords: Simultaneous Local Election, Political Conflict, Democrative Conflict Governance